Cancer survivors' receipt of treatment summaries and implications for patient-centered communication and quality of care. Issue 10 (October 2015) - Blanch-Hartigan, Danielle; Chawla, Neetu; Beckjord, Ellen I.; Forsythe, Laura P.; de Moor, Janet S.; Hesse, Bradford W.; Arora, Neeraj K.
Graphical abstract